An overview of the development of Personal Development Planning (PDP) and e-Portfolio practice in UK higher education - Janet Strivens (Association for Learning Development in Higher Education (ALDinHE), 2010)
This article presents an overview of the origins of Personal Development Planning (PDP) in UK higher education and the development of the concept into a range of practices, rooted in the processes of recording achievement, reflection, review and planning. It reviews the various theoretical underpinnings that have been proposed for PDP and charts how the developing evidence base has become an increasing focus of interest to practitioners and policymakers alike. The role of technology in supporting PDP processes is acknowledged and in particular the close association between PDP and e-Portfolio practices is examined. The article concludes with a look at current initiatives which draw on PDP concepts, the continuing importance of these concepts to educational practice and the size of the research task which still lies ahead.